Impact of the 'Giving Cigarettes is Giving Harm' campaign on knowledge and attitudes of Chinese smokers. (9th May 2014) - Huang, Li-Ling; Thrasher, James F; Jiang, Yuan; Li, Qiang; Fong, Geoffrey T; Chang, Yvette; Walsemann, Katrina M; Friedman, Daniela B
Abstract : Objective: To date there is limited published evidence on the efficacy of tobacco control mass media campaigns in China. This study aimed to evaluate the impact of a mass media campaign 'Giving Cigarettes is Giving Harm' (GCGH) on Chinese smokers' knowledge of smoking-related harms and attitudes towards cigarette gifts. Methods: Population-based, representative data were analysed from a longitudinal cohort of 3709 adult smokers who participated in the International Tobacco Control (ITC) China Survey conducted in six Chinese cities before and after the campaign. Logistic regression models were estimated to examine associations between campaign exposure and attitudes towards cigarette gifts measured post-campaign. Poisson regression models were estimated to assess the effects of campaign exposure on post-campaign knowledge, adjusting for pre-campaign knowledge. Findings: Fourteen percent (n=335) of participants recalled the campaign within the cities where the GCGH campaign was implemented. Participants in the intervention cities who recalled the campaign were more likely to disagree that cigarettes are good gifts (71% vs 58%, p<0.01) and had greater levels of campaign-targeted knowledge than those who did not recall the campaign (mean=1.97 vs 1.62, p<0.01). Disagreeing that cigarettes are good gifts was higher in intervention cities than in control cities. Changes in campaign-targeted knowledge were similar in both cities, perhaps due to a secular trend, low campaign recall or contamination issues. Conclusions: These findings suggest that the GCGH campaign increased knowledge of smoking harms, which could promote downstream cessation. This study provides evidence to support future campaign development to effectively fight the tobacco epidemic in China.